Model-based safety and assessment : 7th International Symposium, IMBSA 2020, Lisbon, Portugal, September 14-16, 2020, Proceedings /: 7th International Symposium, IMBSA 2020, Lisbon, Portugal, September 14-16, 2020, Proceedings. (2020) - Unknown
No abstract available